ANALISIS KINERJA DENGAN MENGGUNAKAN PENDEKATAN BALANCED SCORE CARD PADA PT SEMEN TONASA KABUPATEN PANGKEP - Faradilla Yusmaniar (Journal AK-99, 2021)
This research aims to find out the performance in PT Semen Tonasa if measured using the Balanced Scorecard method. It is hoped that this research can be a reference for further research and add insight and knowledge about the application of balanced scorecards within the company as well as deepen existing theories to be applied in the real world and as comprehensive financial and nonfinan financial information to the company to help decision makers understand the aspects that exist widely. The data collection techniques used are observations, questionnaires and documentation. The type of data used in this study is quantitative data which is data in the form of numbers and qualitative data in the form of narasai. The source of this research data is person, paper and place. Data analysis techniques used to process research data are financial perspective formulas such as profit increase, total cost, ratio analysis later for customer perspective using customer satisfaction formula, then for internal business process perspective using descriptive analysis and learning and growth perspective using customer satisfaction formula. The results showed that overall company performance using a balanced scorecard approach so that the company's performance can be said to be lacking, sufficient, or good. Out of a total of 10 benchmarks used in four balanced scorecard perspectives there are five benchmarks that are considered good implementation namely current ratio, customer satisfaction, innovation, after-sales service, and employee satisfaction, while the other four benchmarks are considered sufficient in implementation and one bad. Based on the overall calculation of the balanced scorecard perspective, it is known that in general the performance of PT. Semen Tonasa Pangkep Regency based on balanced scorecard has reached 90% or is in the category very good or very satisfactory.